Analiz rezul'tatov Cempionata mira - 2019 po chudožestvennoj gimnastike - Terekhina, R. N.; Kryuchek, E. S.; Medvedeva, E. N.; Viner-Usmanova, I. A.; Dveyrina, O. A.; Kolesnikova, T. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The final world championship in the current Olympic cycle was the competition of gymnasts in Baku. Athletes from all Continents of the individual program and group exercises fought for the right to participate in the most prestigious competitions - the Olympics in Tokyo. The sports team of the Russian Federation in rhythmic gymnastics won: in the individual program - six gold, two silver and two bronze medals; in the group - two gold and one bronze medal. This article is devoted to the analysis of the championship results and the balance of power on the world gymnastic platform on the eve of the main start of the four-year period.